Alexithymia Is Associated with Tinnitus Severity - Wielopolski, Jan; Kleinjung, Tobias; Koch, Melanie; Peter, Nicole; Meyer, Martin; Rufer, Michael; Weidt, Steffi (Frontiers in Psychiatry, 2017)
Objective: Alexithymia is considered to be a personality trait with a tendency to express psychological distress in somatic rather than emotional form and, therefore, may play a vital role in somatization. Although, such a propensity can be found in patients suffering from tinnitus, the relationship between alexithymic characteristics and the subjective experience of tinnitus severity remains yet unclear. Our aim was to evaluate which alexithymic characteristics are linked to the subjective experience of tinnitus symptomatology. Methods: We evaluated tinnitus severity (Tinnitus Handicap Inventory, THI), alexithymia (20-item Toronto Alexithymia Scale, TAS-20) and depression (Beck Depression Inventory, BDI) in 207 outpatients with tinnitus. Correlation analyses and multiple regression analyses were calculated in order to investigate the relationship between alexithymic characteristics, tinnitus severity and depression. Results: Highly significant positive correlations were found between THI total score and TAS-20 total score as well as BDI score. Regarding the TAS-20 subscales, multiple regression analyses showed that only the TAS-20 subscale “difficulty in identifying feelings” (DIF) and the BDI significantly predicted the subjective experience of tinnitus severity. Regarding the THI subscales, only higher scores of the THI subscale “functional“ demonstrated an independent moderate association with higher scores for DIF. Conclusion: We found an independent association between the subjective experience of tinnitus severity and alexithymic characteristics, particularly with regard to limitations in the fields of mental, social and physical functioning because of tinnitus and the difficulty of identifying feelings facet of alexithymia. These findings are conducive to a better understanding of affect regulation that may be important for the psychological adaptation of patients suffering from tinnitus.